Investment Liberalization in the ASEAN Economic Community Vietnam’s Participation, Opportunities and Challenges - Nguyen, Thi Minh Phuong (H. : ĐHQGHN, 2017)
Investment liberalization plays an important role in building a single market and production base in the ASEAN Economic Community (AEC). The paper examines Vietnam’s participation in the AEC from the perspective of investment liberalization through analysis of: (i) Vietnam’s commitments and her implementation of commitments under the ASEAN Comprehensive Investment Agreement (ACIA); (ii) the current situation of foreign direct investment (FDI) in ASEAN and Vietnam; and (iii) opportunities and challenges for Vietnam from AEC’s liberalization of investment.